Building a Mystery: Giorgio de Chirico and Italian Renaissance Painting. (2nd January 2019) - Brazeau, Bryan
ABSTRACT: In an infamous 1926 article in La révolution Surréaliste, André Breton roundly condemned Giorgio de Chirico, faintly praising his early 'metaphysical' works, yet rejecting the artist's later production. This judgment has had a marked impact on later criticism, which often separates the artist's work into his early 'metaphysical' period and his production after 1919, when he proclaimed himself a pictor classicus advocating a 'return to craft' that focused on painting as a technical skill and the copying of Renaissance masters. Building on work of recent scholars, this essay investigates de Chirico's relationship to Renaissance painting, arguing that his interest in early modern Italian masters predates his 1919 break with the avant-garde. Through an examination of de Chirico's writings and early metaphysical canvases, the artist's interest in Renaissance paintings is shown to be a constant thread throughout his early career, rather than a reactionary rejection of contemporary artistic currents.